Dual Dopamine Derived Polydopamine Coated N‐Doped Porous Carbon Spheres as a Sulfur Host for High‐Performance Lithium–Sulfur Batteries. Issue 45 (9th July 2019) - Fan, Zengjie; Ding, Bing; Guo, Hongshuai; Shi, Minyuan; Zhang, Yadi; Dong, Shengyang; Zhang, Tengfei; Dou, Hui; Zhang, Xiaogang
Abstract: Lithium–sulfur (Li–S) batteries are considered to be one of the most promising energy storage systems owing to their high energy density and low cost. However, their wide application is still limited by the rapid capacity fading. Herein, polydopamine (PDA)‐coated N‐doped hierarchical porous carbon spheres (NPC@PDA) are reported as sulfur hosts for high‐performance Li‐S batteries. The NPC core with abundant and interconnected pores provides fast electron/ion transport pathways and strong trapping ability towards lithium polysulfide intermediates. The PDA shell could further suppress the loss of lithium polysulfide intermediates through polar–polar interactions. Benefiting from the dual function design, the NPC/S@PDA composite cathode exhibits an initial capacity of 1331 mAh g −1 and remains at 720 mAh g −1 after 200 cycles at 0.5 C. At the pouch cell level with a high sulfur mass loading, the NPC/S@PDA composite cathode still exhibits a high capacity of 1062 mAh g −1 at a current density of 0.4 mA cm −2 . Abstract : Polydopamine (PDA)‐coated N‐doped hierarchical porous carbon spheres (NPC@PDA) are reported as sulfur host for high‐performance Li–S batteries. The NPC core with abundant and interconnected pores provides fast electron/ion transport pathways and strong trapping ability towards lithium polysulfide intermediates. The PDA shell could further suppress the loss of lithium polysulfide intermediates through polar–polar interaction.